Potential role of cholesterol in the migration of neurons containing gonadotropin-releasing hormone - Wadas, Brandon, author; Edelmann, M., author; Spivak, I., author; Feinstein, E., author; Schwarting, G., author; Intlekofer, K., author; Tobet, Stuart, author (Colorado State University. Libraries, 2005)
Signaling by Sonic Hedgehog (Shh) is instrumental in the development of midline facial and forebrain structures. Signaling by Shh can be dependent upon conjugation with cholesterol. Structural abnormalities related to cholesterol depletion may be a result of a failure of Shh signaling. Disorders resulting in cholesterol depletion are often characterized in part by developmental malformations, including holoprosencephaly. Neurons that synthesize gonadotropin releasing hormone (GnRH; controls the reproductive axis) originate in the nasal compartment and migrate into the brain along a route that may depend upon proper Shh signaling. The current study was conducted to assess whether cholesterol-depleted enzyme Dhcr24-/- mice would affect the unique migration of GnRH neurons as they migrate to the brain.
Keywords: Luteinizing hormone releasing hormone -- Synthesis; Cholesterol